2010
DOI: 10.1200/jco.2009.25.5489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Error Rates in Single-Arm Versus Randomized Phase II Cancer Clinical Trials

Abstract: A B S T R A C T PurposeTo improve the understanding of the appropriate design of phase II oncology clinical trials, we compared error rates in single-arm, historically controlled and randomized, concurrently controlled designs. Patients and MethodsWe simulated error rates of both designs separately from individual patient data from a large colorectal cancer phase III trials and statistical models, which take into account random and systematic variation in historical control data. ResultsIn single-arm trials, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 25 publications
0
65
0
Order By: Relevance
“…These results suggest that a single-arm phase II study with a primary endpoint of ORR may not be adequate to evaluate the efficacy of second-line chemotherapy for AGC. Randomised phase II studies that compare standard treatments and investigational treatments may be better methods of screening for effective treatments to include within phase III trials [26].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a single-arm phase II study with a primary endpoint of ORR may not be adequate to evaluate the efficacy of second-line chemotherapy for AGC. Randomised phase II studies that compare standard treatments and investigational treatments may be better methods of screening for effective treatments to include within phase III trials [26].…”
Section: Discussionmentioning
confidence: 99%
“…The use of categorical response criteria magnifies the impact of measurement variability, whereas comparisons of continuous data minimize this impact. Tang and colleagues showed that, in single-arm phase II trials with RECIST response rate as the primary endpoint, small errors in historical response rate assumptions can result in a 2-to 4-fold increase in the rate of phase II trials that are falsely interpreted as positive (24). Randomization could minimize erroneous conclusions based on RECIST-based endpoints, but the power of such trials would lag behind the power of trials that use comparisons of continuous data.…”
Section: Recist Falls Short Of the New Paradigmmentioning
confidence: 99%
“…There are many possible designs of a Phase II oncology trial (1), and randomized Phase II trials are often recommended (2)(3)(4)(5). In such randomized trials, patients' tumors are assessed through radiographic imaging, and Response Evaluation Criteria in Solid Tumors (RECIST) criteria (6) applied for determination of tumor burden, tumor response, and progression-free survival (PFS), defined as the earlier of the occurrence of progressive disease or death.…”
Section: Introductionmentioning
confidence: 99%